Harmonic Reduction in Multilevel Inverter Based on Super Capacitor as a Storage - Mohammed Rasheed; Rosli Omar; Marizan Sulaiman (Institute of Advanced Engineering and Science, 2015)
Cascaded H-Bridge multilevel inverter has become more attractive to generate high power in an electrical distribution system. This paper discusses the control of five level cascaded H-bridge multilevel inverter with super capacitor as a Dc energy storage. The control of the multilevel inverter using PI and space vector pulse width modulation (SVPWM) controllers based on the modelling and Simulink of cascaded H-bridge can observe the effectiveness of the proposed control to reduce harmonic contents of the multilevel inverter output. High frequency ripple from the inverters can be removed from the system using low voltage filter. Total harmonic distortion (THD) for both current and voltage is quite low to meet the IEEE standard. Modelling of the system has been done using MATLAB/Simulink.